Microclad and lspr-enhanced hollow-core anti-resonant optical fiber and methods of performance tuning thereof

CN122902002APending Publication Date: 2026-10-13WUXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077170.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

现有空芯反谐振光纤的光学性能完全由静态的几何结构决定,导致性能固化,无法适配不同应用场景或补偿工艺误差;且为提升一些特定性能,多依赖于复杂的结构异构,导致制备难度大

Benefits of technology

[0055]有益效果:本发明的一种微包层和LSPR增强的空芯反谐振光纤及其性能调谐方法,通过在传统单层或多层反谐振玻璃膜层的外部,引入一层具有特定折射率分布的梯度折射率微包层,提供了额外的光场回拉机制,协同反谐振效应,实现了接近理论极限的低损耗;还在该微包层的基质中均匀或梯度地分散金属纳米粒子,实现了基于LSPR效应的动态或准静态性能调谐,突破了传统光纤的静态限制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122902002A_ABST
    Figure CN122902002A_ABST
Patent Text Reader

Abstract

The application discloses a kind of microcladding and LSPR enhanced hollow core anti-resonant optical fiber and its performance tuning method, including core, for guiding optical wave transmission along axial direction;Cladding structure is located at the periphery of core, including the circumferentially distributed M anti-resonant unit;Anti-resonant unit includes anti-resonant structure layer, for forming anti-resonant reflection interface, limit optical field in core;Anti-resonant structure layer is coated with microcladding on the outside of optical fiber radial, microcladding has non-resonant reflection mechanism, when optical field enters microcladding, its propagation path is bent and is guided back to the direction of core;Microcladding is built-in with metal nanostructure, metal nanostructure produces localized surface plasmon resonance enhancement in microcladding, so that microcladding is the functional layer of dynamic regulation and control for optical fiber waveguide characteristics.The application realizes dynamic or quasi-static performance tuning based on LSPR effect, and cooperatively optimizes restriction loss, bending loss and dispersion, and avoids excessive complication caused by improving specific performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical fiber technology, and in particular to a microcladding and LSPR-enhanced hollow-core antiresonant optical fiber and its performance tuning method. Background Technology

[0002] Hollow-core antiresonant fiber (HC-ARF) effectively suppresses optical field leakage through its ingenious cladding structure, while simultaneously achieving broadband, low loss, low bending loss, and high mode purity. The optical performance of existing HC-ARF fibers is entirely determined by their static geometry, resulting in rigid performance that cannot adapt to different application scenarios or compensate for process errors. Furthermore, improving certain specific properties often relies on complex structural heterogeneity, leading to significant fabrication difficulties. Therefore, there is an urgent need for a technical solution that can synergistically optimize optical field confinement, bending insensitivity, and dispersion characteristics without significantly increasing structural complexity or fabrication difficulty. Summary of the Invention

[0003] Purpose of the invention: In order to overcome the shortcomings of the prior art, the present invention provides a hollow anti-resonant optical fiber enhanced by microcladding and LSPR and its performance tuning method. By constructing a gradient refractive index microcladding and introducing the LSPR effect, dynamic and multi-dimensional control of the fiber guiding characteristics can be achieved, fundamentally solving the problem of conflict between performance solidification and multi-objective optimization in the prior art, and avoiding excessive structural complexity caused by improving specific performance.

[0004] Technical Solution: To achieve the above objectives, the present invention provides a micro-clad and LSPR-enhanced hollow-core anti-resonant optical fiber, comprising a core and a cladding structure; the core is located at the center of the optical fiber and is used to guide light waves to propagate along the axial direction, and the core is composed of a low-refractive-index medium; the cladding structure is located around the core and includes an inner cladding and an outer cladding, the inner cladding being composed of M anti-resonant units distributed circumferentially uniformly or symmetrically, where M is an integer greater than or equal to 6, preferably 6, 8, or 10; the outer cladding is composed of a uniform quartz glass or chalcogenide glass material, providing mechanical support for the optical fiber and a basic cladding boundary.

[0005] There are gaps between two adjacent anti-resonant units and between the inner cladding and the outer cladding; these gaps are interconnected with the internal cavity of each anti-resonant unit and the fiber core and are filled with air or inert gas.

[0006] The anti-resonance unit includes an anti-resonance structure layer for forming an anti-resonance reflection interface, confining the light field within the fiber core; the wall thickness t of the anti-resonance structure layer satisfies the anti-resonance condition:

[0007] ;

[0008] Where m is the anti-resonance order, taking the value of 1, 2, or 3; λ0 is the target operating wavelength, ranging from 1.0 to 4.0 μm, and the ratio of the fiber core diameter d to the target operating wavelength λ0 is d / λ0 ∈ [20, 60]; n g is the refractive index of the anti-resonant structure layer material.

[0009] The anti-resonant structure layer has a micro-cladding layer on the outer side of the optical fiber in the radial direction, which is used to control the leakage mode and mode field distribution of the optical field. The micro-cladding layer has a non-resonant reflection mechanism. When the optical field enters the micro-cladding layer, its propagation path is bent and guided back to the fiber core direction.

[0010] The microcladding layer contains a built-in metal nanostructure, which generates localized surface plasmon resonance enhancement in the microcladding layer, making the microcladding layer a functional layer for dynamically controlling the wave conduction characteristics of the optical fiber.

[0011] Furthermore, the anti-resonance structure layer has an arc-shaped cross-section structure, with the side facing the fiber core being the open side. The C-shaped opening facing the fiber core is used to ensure the integrity of the glass-air interface, which is a prerequisite for realizing the anti-resonance effect. Both sides are low-refractive-index media, such as air, to form a Fabry-Perot etalon.

[0012] Furthermore, the refractive index of the micro-cladding layer monotonically decreases from the inside to the outside along its own radial direction; the refractive index distribution of the micro-cladding layer satisfies:

[0013] , ;

[0014] Where, n in R is the refractive index of the material at the inner surface of the microcladding. in R is the inner diameter of the microcladment. out The outer diameter of the micro-cladding layer; the refractive index n of the material at the inner surface of the micro-cladding layer. in The value ranges from 1.44 to 2.80, and the refractive index n of the material at its outer surface is... out The value range of α is 1.40 to 2.40; α is the gradient exponent, and its value range is 0.5 ≤ α ≤ 2.0. By adjusting α, the propagation path of the light field within the microcladding is changed to obtain the lowest bending loss α. bend .

[0015] Furthermore, the metal nanostructure includes several metal nanoparticles, which are uniformly or gradiently dispersed in the matrix of the micro-cladding layer; used to generate localized surface plasmon resonance.

[0016] When the plurality of metal nanoparticles are gradient dispersed in the matrix of the microcoating, their concentration monotonically increases radially from the inside to the outside, and their distribution satisfies:

[0017] ;

[0018] Where C0 is the maximum concentration. This is the concentration distribution index, and its value ranges from 0.5 to 1. ≤2.0.

[0019] Furthermore, the total loss α of the optical fiber total Including limiting loss α CL Bending loss α bend Scattering loss α scat and LSPR absorption loss α LSPR The LSPR absorption loss α LSPR The distribution along the fiber axis satisfies:

[0020] ;

[0021] By adjusting the gradient index α and the concentration distribution index The total fiber loss α at the target wavelength is reduced. total Minimum.

[0022] Furthermore, the LSPR effect generated by the metal nanostructure is used to selectively suppress higher-order modes. For higher-order modes with an angular order of I, the coupling loss enhancement factor η between the metal nanoparticles and the higher-order modes is increased. l Represented as:

[0023] ;

[0024] in, The limiting loss for the I-th order mode, For the limiting loss of the fundamental mode, S LSPR E represents the distribution region of metal nanoparticles. l and E 01 These represent the electric field intensity of the corresponding mode in the LSPR region.

[0025] The LSPR absorption cross section of the metal nanoparticle at wavelength λ is described by the following relationship:

[0026] ;

[0027] Q is the quality factor, ranging from 5 to 20, and σ is the coupling coefficient.

[0028] When the metal nanoparticles are spherical, the metal nanostructure, by selecting the material, particle size, and concentration distribution of the metal nanoparticles, matches the LSPR wavelength with the operating wavelength of the higher-order modes that need to be suppressed in the optical fiber; wherein, the characteristic size D of the metal nanoparticles... pThe local surface plasmon resonance condition under the spherical electrostatic approximation is satisfied as follows:

[0029] When D p =λ LSPR ;

[0030] Where, λ LSPR For the target local surface plasmon resonance wavelength, ε m ε is the real part of the dielectric constant of the metal nanoparticle material. eff The effective dielectric constant of the micro-cladding in the particle distribution region is denoted as .

[0031] Furthermore, when the metal nanoparticles are non-spherical, such as rod-shaped or shell-shaped, an anisotropic LSPR response is generated by directionally arranging the metal nanoparticles, introducing polarization-dependent loss in the optical fiber that is complementary to geometric birefringence.

[0032] Furthermore, the group velocity dispersion D of the hollow antiresonant fiber is determined by the waveguide dispersion D. w and material dispersion D m Composition; wherein, the waveguide dispersion D w Related to the gradient exponent α, adjusting the gradient exponent α can achieve a translation of the zero-dispersion wavelength within the target band. The formula for calculating the group velocity dispersion D is:

[0033] ;

[0034] in, n is the propagation constant of the fundamental mode. eff Obtained through numerical simulation or analytical modeling.

[0035] Furthermore, the anti-resonant structure layer is composed of one or more anti-resonant glass film layers, and the material is silicon dioxide or chalcogenide glass; the matrix of the micro-cladding layer is silicon dioxide doped with GeO2 or B2O3, or chalcogenide glass with a graded composition; the material of the metal nanoparticles is one of gold, silver, platinum, copper or an alloy thereof.

[0036] Furthermore, a performance tuning method for the hollow-core antiresonant optical fiber:

[0037] By adjusting the gradient exponent α to change the propagation path of the light field within the microcladding, the lowest bending loss can be obtained.

[0038] By adjusting the gradient exponent α to continuously change the position of the zero-dispersion point and the dispersion slope of the optical fiber, the zero-dispersion wavelength can be shifted within the target band.

[0039] By adjusting the gradient exponent α and the concentration distribution exponent This minimizes the total fiber loss at the target wavelength.

[0040] By selecting the shape, particle size, and concentration distribution of metal nanoparticles, their LSPR wavelength λ can be optimized. LSPR The absorption effect or local field enhancement effect is controlled by matching or detuning the target operating wavelength λ0.

[0041] For high-power ultrashort pulse transmission, by setting λ LSPR The detuning of λ0 is between 5% and 15%, which prevents the LSPR from absorbing fundamental mode energy and enhances Kerr nonlinearity through hotspot effect to compensate for self-phase modulation and suppress pulse distortion.

[0042] For selective mode suppression, by adjusting λ LSPR It matches the resonant wavelength of higher-order modes, preferentially absorbs higher-order mode energy, and improves single-mode purity.

[0043] Furthermore, a high-power ultrashort pulse laser transmission system includes the hollow-core anti-resonant fiber, an ultrafast laser source, and a coupling optical system; the coupling optical system is used to couple the laser output from the ultrafast laser source to the core of the hollow-core anti-resonant fiber, wherein the peak power of the output pulse from the ultrafast laser source is greater than 1MW and the pulse width is less than 100ps.

[0044] Wherein, the localized surface plasmon resonance wavelength λ LSPR With respect to the center wavelength λ of the ultrafast laser source pump Satisfy the mistuning relationship:

[0045] ;

[0046] This detuning means that the LSPR effect does not directly absorb the fundamental mode energy, but instead compensates for nonlinear distortion by enhancing the Kerr effect through a local field.

[0047] Furthermore, a method for fabricating the hollow-core anti-resonant optical fiber includes the following steps:

[0048] S1. Using an improved chemical vapor deposition (MCVD) process, porous deposition layers with decreasing refractive index are formed sequentially from the inside to the outside in the radial direction. After depositing the Nth layer, the deposition is paused and a metal nanostructure is prepared to obtain a capillary with a radially gradient refractive index and an internal metal nanostructure.

[0049] Wherein, N is 60%-80% of the total number of deposited layers; when preparing metal nanostructures, the deposited porous layer is immersed in a metal ion solution, and under preset conditions, the metal ions are reduced and aggregated to form metal nanoparticles dispersed in the porous layer. The particle concentration distribution is controlled by adjusting the immersion time and the porosity of each layer.

[0050] S2. Grind the capillary into a cylindrical structure with a preset inner diameter and thickness as a micro-coating layer, deposit an anti-resonance structure layer of preset thickness on the inner wall of the cylindrical structure, and finally cut to form a single-sided open anti-resonance unit preform.

[0051] S3. Assemble the M anti-resonant unit preforms into a relatively fixed position with an outer jacket tube according to the preset circumferential distribution to form a stable optical fiber preform structure.

[0052] S4. The optical fiber preform structure is drawn into the final optical fiber through a drawing process, so that the outer diameter of the final optical fiber is stabilized at 120-200μm; the drawn optical fiber is coated with a protective layer to complete the preparation.

[0053] Furthermore, an alternative method for preparing metal nanostructures in step S1 includes: during chemical vapor deposition, introducing an organometallic compound in vapor form along with the reaction gas into the deposition zone, decomposing it at high temperature to form nanoparticles, and controlling the size and radial distribution of the nanoparticles by adjusting the flow rate of the organometallic source and the deposition temperature; wherein the organometallic compound includes gold hexafluoroacetylacetone, silver trifluoroacetate, etc.; and the high temperature condition is 1100-1300℃.

[0054] Alternatively, after the optical fiber is drawn, a sol or gel containing metal nanoparticles can be injected into a specific area of ​​the microcladding using a microfluidic method, and then fixed by heat treatment.

[0055] Beneficial effects: The present invention discloses a microcladding and LSPR-enhanced hollow anti-resonant optical fiber and its performance tuning method. By introducing a gradient refractive index microcladding with a specific refractive index distribution outside the conventional single-layer or multi-layer anti-resonant glass film, an additional optical field pull-back mechanism is provided, which, in conjunction with the anti-resonance effect, achieves low loss close to the theoretical limit. Furthermore, metal nanoparticles are uniformly or gradiently dispersed in the matrix of the microcladding, realizing dynamic or quasi-static performance tuning based on the LSPR effect, breaking through the static limitations of traditional optical fibers.

[0056] In terms of fabrication methods, mature processes such as MCVD / PCVD are used to prepare gradient refractive index microcladdings, avoiding extremely complex geometric structures and improving the success rate and consistency of fiber fabrication. Based on the characteristics of each structural layer and the physical formulas they satisfy, quantitative guidance for ray design is achieved, significantly reducing the number of simulation and experimental iterations.

[0057] Furthermore, the fiber mode field has minimal overlap with the cladding material, and the LSPR is designed in the detuned region of the weak absorption region. This fiber has an extremely high damage threshold and is suitable for high-power ultrashort pulse transmission. Attached Figure Description

[0058] Figure 1This is a schematic diagram of the cross-sectional structure of the hollow anti-resonant optical fiber according to Embodiment 1 of the present invention.

[0059] Figure 2 This is a partially enlarged schematic diagram of a single anti-resonant unit structure.

[0060] Figure 3 This is a comparison of the confined loss spectra of Embodiment 1 of the present invention and conventional hollow-core anti-resonant fiber (HC-ARF).

[0061] Figure 4 This is a curve showing the change of bending loss with gradient exponent α in Embodiment 2 of the present invention.

[0062] Figure 5 This is a comparison diagram of mid-infrared spectral broadening in Embodiment 3 of the present invention.

[0063] Figure 6 This is a comparison diagram of group velocity dispersion (GVD) in Embodiment 4 of the present invention. Detailed Implementation

[0064] The invention will now be further described with reference to the accompanying drawings.

[0065] As attached Figure 1-6 The aforementioned microcladding and LSPR-enhanced hollow anti-resonant optical fiber includes a fiber core 1 and a cladding structure; the cladding structure includes an inner cladding and an outer cladding 3, wherein the outer cladding 3 is composed of a uniform quartz glass or chalcogenide glass material, providing mechanical support for the optical fiber and a basic cladding boundary.

[0066] The inner cladding is composed of M anti-resonant units 2 that are circumferentially uniform or symmetrically distributed, where M is an integer greater than or equal to 6, preferably 6, 8 or 10; all anti-resonant units 2 surround to form the fiber core 1, which is an air fiber core or a fiber core of other low refractive index media, used to guide light waves to propagate along the axial direction.

[0067] Each anti-resonant unit 2 has a C-shaped opening structure with the C-shaped opening facing the fiber core. The anti-resonant unit 2 includes an anti-resonant structure layer 21, composed of one or more arc-shaped anti-resonant glass films made of silicon dioxide or chalcogenide glass; both sides of the layer are low-refractive-index media to form a Fabry-Perot interference. This layer forms an anti-resonant reflection interface, confining the light field within the fiber core 1. The outer side of the anti-resonant structure layer 21 in the radial direction of the optical fiber is covered with a micro-cladding layer 22, which is used to modulate the leakage modes and mode field distribution of the light field.

[0068] Based on the structure of the single anti-resonant unit 2 described above, in the hollow-core anti-resonant optical fiber of this scheme, the inner and outer surfaces of the C-shaped anti-resonant glass film constitute the two reflecting surfaces of the Fabry-Perot interference; its inner surface is the side facing the fiber core, and its outer surface is the side facing the micro-cladding 22. The micro-cladding 22 is composed of a low-refractive-index medium. The principle is that only when both sides of the glass film are low-refractive-index media can a sufficient refractive index difference (Δn ≈ 0.4~0.8) be formed, making the Fresnel reflection coefficient sufficiently large, thereby achieving efficient anti-resonant reflection. If one side is a high-refractive-index medium, such as a quartz cladding, the reflection effect will be significantly weakened.

[0069] Light is incident from the air fiber core at a grazing incidence (i.e., an incident angle close to 90°) onto the inner surface of the glass film. Part of the light is reflected back to the fiber core at the inner surface, while the other part is transmitted into the glass film, propagating within the glass layer to the outer surface, where it undergoes partial reflection and transmission again. The light transmitted through the outer surface enters the micro-cladding layer 22, while the light reflected back into the glass layer is reflected again at the inner surface, and this process repeats.

[0070] Although the glass film layer is macroscopically a curved C-shaped arc structure, it can be approximated as a plane in local regions under wavelength scale and grazing incidence conditions. The multi-beam interference theory still holds locally. According to optical thin film theory, any two parallel reflecting interfaces can constitute an etalon; therefore, the resonant cavity formed between the two reflecting surfaces of the anti-resonant structure layer 21 constitutes a Fabry-Perot etalon.

[0071] Furthermore, the C-shaped opening of the anti-resonance structure layer 21, facing the fiber core, is designed to ensure the integrity of the glass-air interface, thus preventing Fabry-Perot interference failure. The principle is that the anti-resonance effect is essentially the reflection of light by the glass-air interface. The C-shaped opening facing the fiber core means that: on one hand, the inner surface of the film is completely exposed to the air fiber core, without any glass support obstruction, ensuring a complete glass-air interface on the inner surface. On the other hand, the outer surface of the film is completely exposed to air or the low-refractive-index micro-cladding layer 22, similarly ensuring a complete glass-air interface. If the C-shaped opening faces other directions, the inner side of the film will be partially covered by the glass support, resulting in an incomplete interface and disrupting the anti-resonance effect. If the opening faces outwards, the inner side of the film needs to be attached to the support structure, turning some areas into glass-glass interfaces, changing the reflection conditions, and introducing Fano resonance, increasing losses. Only when the opening faces the fiber core can the arc-shaped region of each unit be suspended in the air environment, ensuring that all areas where the light field interacts with the glass are clean glass-air interfaces.

[0072] In summary, the inner and outer surfaces of the anti-resonance structure layer 21 form a pair of reflective interfaces, with its inner surface fully exposed to the air fiber core and its outer surface similarly exposed to the micro-cladding layer 22 of the low-refractive-index medium, thus forming an equivalent Fabry-Perot resonant cavity. When the film thickness satisfies the anti-resonance condition, light leaking from the fiber core undergoes multi-beam interference between the two interfaces, while transmitted light exhibits destructive interference, maximizing reflectivity.

[0073] The wall thickness t of the anti-resonance structure layer 21 satisfies the anti-resonance condition:

[0074] ;

[0075] Where m is the anti-resonance order, taking the value of 1, 2, or 3; λ0 is the target operating wavelength, ranging from 1.0 to 4.0 μm, and the ratio of the diameter d of the fiber core 1 to the target operating wavelength λ0 is d / λ0 ∈ [20, 60]; n g Let t be the refractive index of the anti-resonant structural layer 21. According to thin-film interference theory, when the film thickness t of the anti-resonant structural layer 21 satisfies the above adjustment, the transmitted light undergoes destructive interference, and the reflectivity is close to 1.

[0076] More preferably, the micro-cladding layer 22 is a refractive index gradient layer, whose refractive index decreases monotonically from the inside to the outside along its own radial direction, forming an equivalent rainbow defect; this gradient layer can generate a pullback effect on the light field that leaks into the layer. When the light field enters the micro-cladding layer 22, its propagation path is bent and guided back to the fiber core direction, instead of directly shooting towards the high-loss outer cladding layer. This is equivalent to adding an additional, non-resonant light reflection mechanism, which can effectively and significantly reduce confinement loss and bending loss without increasing the number of anti-resonant glass film layers.

[0077] Specifically, the refractive index distribution of the micro-cladding layer 22 satisfies:

[0078] , ;

[0079] Where, n in R is the refractive index of the material at the inner surface of the microcladding 22. in R is the inner diameter of the microcladding 22. out The outer diameter of the micro-cladding layer 22; the refractive index n of the material at the inner surface of the micro-cladding layer 22. in The value ranges from 1.44 to 2.80, and the refractive index n of the material at its outer surface is... out The value range is 1.40 to 2.40.

[0080] α is the gradient exponent, with a value ranging from 0.5 to 2.0. By adjusting α to change the propagation path of the light field within the micro-cladding 22, the pullback effect can be optimized to obtain the lowest bending loss α. bend .

[0081] Furthermore, unlike traditional hollow antiresonant fibers where dispersion is primarily influenced by the core diameter, this scheme introduces an additional waveguide dispersion term through the gradient refractive index distribution of the microcladding 22, thus transforming the group velocity dispersion D of the hollow antiresonant fiber into the waveguide dispersion D... w and material dispersion D m Composition; the formula for calculating the group velocity dispersion D is:

[0082] ;

[0083] In the formula, n is the propagation constant of the fundamental mode. eff Obtained through numerical simulation or analytical modeling.

[0084] Wherein, the waveguide dispersion D w Related to the gradient exponent α, by adjusting the gradient exponent α, the position of the zero-dispersion point and the dispersion slope of the optical fiber can be continuously changed to achieve the translation of the zero-dispersion wavelength in the target band, providing a more flexible design space for supercontinuum generation and pulse compression.

[0085] Based on the gradient refractive index distribution, the microcladding 22 also incorporates a metal nanostructure, which includes several metal nanoparticles 221. These metal nanoparticles 221 are uniformly or gradient-dispersed in the matrix of the microcladding 22. Due to the collective electronic oscillation of the metal nanoparticles at a specific wavelength, extremely strong local field enhancement and characteristic absorption are generated, thereby producing a local surface plasmon resonance (LSPR) effect in the microcladding 22. That is, when the incident light wavelength matches its local surface plasmon resonance wavelength, strong light absorption and scattering are generated. Based on this LSPR effect, the microcladding 22 becomes a functional layer for dynamically controlling the optical fiber guidance characteristics.

[0086] Specifically, the following functions can be achieved:

[0087] Function 1: Selectively suppressing higher-order modes. The metal nanostructure, through the rational design of the type, size, shape, and concentration distribution of its metal nanoparticles 221, matches its LSPR wavelength with the operating wavelength of the higher-order modes to be suppressed in the optical fiber; these higher-order modes include LP11, LP21, etc. Because the mode field of higher-order modes is closer to the cladding structure and interacts more strongly with the nanoparticles, they are preferentially attenuated, thereby improving the single-mode performance of the optical fiber.

[0088] Specifically, for higher-order modes with an angular order of I, the coupling loss enhancement factor η with metal nanoparticles... l Represented as:

[0089] ;

[0090] in, The limiting loss for the I-th order mode, For the limiting loss of the fundamental mode, S LSPR E represents the distribution region of metal nanoparticles. l and E 01 These represent the electric field intensity of the corresponding mode in the LSPR region.

[0091] The LSPR absorption cross section of the metal nanoparticle at wavelength λ is described by the following relationship:

[0092] ;

[0093] Q is the quality factor, ranging from 5 to 20, and σ is the coupling coefficient.

[0094] Specifically, when the metal nanoparticles 221 are spherical, their resonant wavelength λ LSPR Particle size D p And the relationship between the surrounding dielectric constants satisfies the local surface plasmon resonance condition under the spherical electrostatic approximation:

[0095] When D p =λ LSPR ;

[0096] Where, λ LSPR For the target local surface plasmon resonance wavelength, ε m ε is the real part of the dielectric constant of the metal nanoparticle material. eff The effective dielectric constant of the micro-cladding 22 in the particle distribution region is given. Therefore, for spherical particles, the LSPR peak can be aligned with the wavelength of higher-order modes by designing the particle size and concentration distribution.

[0097] Function 2: Used to achieve tunable nonlinear enhancement. Since the LSPR effect has a strong local electric field enhancement characteristic, it can significantly enhance the nonlinear optical effect in this region. This nonlinear enhancement effect can be dynamically turned on or off by external optical pumping or electric field excitation.

[0098] In this process, under the action of external optical pumping, by setting the detuning amount between the pump light and the LSPR peak, the LSPR can compensate for nonlinear distortion by enhancing the Kerr effect through the local field at high power.

[0099] Specifically, a high-power ultrashort pulse laser transmission system includes the hollow-core anti-resonant fiber, an ultrafast laser source, and a coupling optical system; the coupling optical system is used to couple the laser output from the ultrafast laser source to the fiber core 1, wherein the peak power of the output pulse from the ultrafast laser source is greater than 1MW and the pulse width is less than 100ps.

[0100] Wherein, the localized surface plasmon resonance wavelength λ LSPR With respect to the center wavelength λ of the ultrafast laser source pump Satisfy the mistuning relationship:

[0101] ;

[0102] That is, the detuning amount is designed to be between 5% and 15%. This detuning amount makes the LSPR effect not directly absorb the fundamental mode energy, but enhance the Kerr effect through the local field to compensate for the self-phase modulation caused by material nonlinearity during transmission, thereby suppressing pulse distortion.

[0103] Function 3: When the metal nanoparticles 221 are non-spherical, such as rods or shells, an anisotropic LSPR response can be generated by directionally arranging the metal nanoparticles 221, thereby introducing polarization-dependent loss that is complementary to geometric birefringence in the optical fiber to help achieve high-performance polarization maintenance.

[0104] Preferably, the plurality of metal nanoparticles 221 are gradient-dispersed in the matrix of the microcoating 22, and their concentration monotonically increases radially from the inside to the outside, and their distribution satisfies:

[0105] ;

[0106] Where C0 is the maximum concentration. This is the concentration distribution index, and its value ranges from 0.5 to 1. ≤2.0.

[0107] In addition, the total loss α of the optical fiber total Including limiting loss α CL Bending loss α bend Scattering loss α scat and LSPR absorption loss α LSPR The LSPR absorption loss α LSPR The distribution along the fiber axis satisfies:

[0108] ;

[0109] Based on the gradient distribution characteristics and total loss calculation method of this metal nanoparticle 221, the gradient index α and the concentration distribution index can be jointly adjusted. The total fiber loss α at the target wavelength is reduced. total Minimization provides explicit mathematical guidance for the multi-objective optimization of optical fibers.

[0110] Optionally, the matrix of the micro-cladding layer 22 is silicon dioxide doped with GeO2 or B2O3, or a chalcogenide glass with a graded composition; the material of the metal nanoparticles 221 is one of gold, silver, platinum, copper, or an alloy thereof.

[0111] Based on the above-described hollow anti-resonant fiber structure, a method for fabricating the hollow anti-resonant fiber is provided, comprising the following steps:

[0112] Step S1: Prepare a gradient refractive index glass rod.

[0113] S11. Install the quartz liner on the lathe.

[0114] S12. At 800-1200℃, a mixed vapor of SiCl4, GeCl4, and POCl3 is introduced. The flow ratio of GeCl4 and POCl3 is changed layer by layer by a mass flow controller. Porous glass layers with decreasing refractive index are deposited radially from the inside to the outside. The thickness of each layer is controlled at 0.5-2 µm, and the total number of deposited layers is 50-200, so that the final refractive index distribution meets the requirements of micro-cladding layer 22.

[0115] S13. After depositing the Nth layer, approximately 60%-80% of the total layers, the deposition is paused. At room temperature, the porous layer is immersed in a 0.001-0.01 mol / L solution of chloroauric acid (HAuCl4) or silver nitrate (AgNO3) for 10-60 min, followed by drying at 100℃. Finally, sintering is carried out at 1200-1400℃ by introducing Cl2 and O2, which reduces and aggregates the metal ions to form metal nanoparticles with a diameter of 5-50 nm. The particle concentration distribution is controlled by adjusting the immersion time and the porosity of each layer.

[0116] S14. After deposition, the substrate tube is shrunk into a solid gradient refractive index glass rod at 1800-2000℃, and the gas pressure inside the tube is kept at 80-120 kPa during the shrunk process.

[0117] Step S2: Prepare the composite anti-resonant unit preform.

[0118] S21. The gradient refractive index glass rod obtained in step S1 is machined to 8-12 mm on a precision cylindrical grinding machine, and then a through hole with an inner diameter of 5-7 mm is machined in its center using an ultrasonic drilling machine to form a cylindrical structure as a gradient refractive index micro-cladding layer 22.

[0119] S22. Using in-tube film deposition or plasma-enhanced chemical vapor deposition, a pure silicon dioxide layer is deposited on the inner wall of the cylinder, with the deposition thickness controlled between 0.3-1.5 µm. Then, a smooth arc-shaped anti-resonant glass film layer 21 is formed by polishing with an oxyhydrogen flame.

[0120] S23. The cylinder after deposition is cut and cleaned at the end face to obtain a preform of a single anti-resonance structural unit 2.

[0121] Step S3: Assemble the optical fiber preform.

[0122] S31. Provide a quartz outer tube with an inner diameter of 20-30 mm and a wall thickness of 2-4 mm.

[0123] S32. Insert the composite anti-resonant unit preforms obtained in the M steps of S2 into the quartz outer tube at equal intervals according to the designed circumferential angle, so that the inner sides of each arc-shaped anti-resonant glass film layer together form an air fiber core.

[0124] S33. Insert thin quartz support rods into the gaps between each prefabricated component and the outer tube to fix the position, ensuring that the center of all anti-resonance units 2 is located on the circumference concentric with the outer tube.

[0125] S34. The assembled structure is vertically fixed on the preform clamp of the fiber drawing tower, and the two ends are lightly fused with an oxyhydrogen flame to form a stable fiber preform.

[0126] Step S4: Fiber drawing.

[0127] S41. Place the optical fiber preform obtained in step S3 into the high-temperature graphite furnace of the optical fiber drawing tower. The temperature inside the furnace is controlled within the range of 1800-2100℃.

[0128] S42. Argon gas is introduced into the inner cavities of fiber core 1 and each anti-resonance unit 2, respectively, and the gas pressure is controlled as follows: fiber core gas pressure P core = 0.5-2 kPa, unit internal air pressure P clad = 5-20 kPa, and P clad >P core .

[0129] S43. The fiber is drawn at a feed rate of 5-50 mm / min and a traction rate of 1-20 m / min. The outer diameter of the fiber is monitored in real time, and the traction speed is adjusted through a feedback control system to stabilize the outer diameter of the fiber at 120-200 µm.

[0130] S44. After passing through an online coating device, the drawn optical fiber is coated with an acrylate or polyimide coating, cured by ultraviolet light, and then wound up.

[0131] Example 1 provides an ultra-low loss width optical fiber for the 1.55μm communication band.

[0132] like Figure 1 As shown, its inner cladding consists of 6 anti-resonant units 2 arranged at equal intervals along the circumference; its air fiber core has a diameter d=30μm and d / λ0≈19.4.

[0133] The anti-resonant structure layer 21 is made of pure SiO2, with λ0 = 1.55 μm, m = 2, and n g =1.444, and the calculated wall thickness t = 1.10 μm.

[0134] The matrix of the micro-cladding layer 22 is selected as GeO2-doped silicon dioxide, n in =1.46 (GeO2 10mol%), n out =1.44, R in =20 μm, R out =35 μm, α=0.8.

[0135] The metal nanoparticles 221 are selected from Au nanospheres, and λ LSPR Designed to be 1.55μm, ε m ≈-95, ε eff ≈2.1, the calculated average diameter D p =15nm, concentration distribution κ=1.5, maximum concentration C0 corresponds to a volume fill rate of 0.5%.

[0136] Prepare according to steps S1-S4 described above.

[0137] Specifically, in step S1, during the deposition process, the GeCl4 flow rate is controlled to decrease layer by layer from 40 sccm to 0. The total number of deposited layers is 150. When 100 layers are deposited, the porous layer is immersed in a 0.005 mol / L HAuCl4 solution for 30 minutes. After sintering, the size of the nanoparticles is approximately 15 nm. The outer diameter of the solid glass rod after melting and shrinking is 10 mm.

[0138] In step S2, the outer diameter of the solid glass is ground to 9 mm, and an inner hole with an inner diameter of 6 mm is machined in the center; a 1.10 μm thick layer of pure SiO2 is deposited using PECVD.

[0139] In step S3, six prefabricated parts are inserted at equal angles into an outer tube with an inner diameter of 25 mm.

[0140] In step S4, the drawing temperature is set to 1950℃, the core air pressure to 1kPa, the internal air pressure of each unit to 12kPa, the traction speed to 10m / min, and the final outer diameter of the optical fiber is controlled at 150μm.

[0141] like Figure 3The figure shows a comparison of the confined loss spectrum of this embodiment and that of conventional HC-ARF (simulation and actual measurement). In the figure, the loss of conventional fiber at 1.55 μm is approximately 0.2 dB / km, with large loss fluctuations within the C+L band. In contrast, the measured total loss of the fiber in this embodiment at 1.55 μm is only 0.08 dB / km, and remains below 0.1 dB / km in the 1530-1625 nm range. Therefore, compared to conventional fiber, the fiber in this embodiment reduces confined loss by more than 60% due to the synergistic effect of the gradient layer and anti-resonant layer; the LSPR absorption peak is designed near 1.55 μm but contributes only 0.01 dB / km of fundamental mode absorption, without affecting the low-loss window; and the broadband flat loss characteristic breaks the limitation of large loss spectrum fluctuations in traditional HC-ARF. Therefore, this embodiment verifies that it achieves ultra-low loss, broadband flat communication band transmission, surpassing the performance of existing hollow-core anti-resonant fibers.

[0142] Example 2 provides a low bending loss optical fiber for the 532nm green light band.

[0143] Based on Example 1, the core diameter of the air fiber is scaled up proportionally by λ0=532nm, resulting in an air core diameter of d=18μm.

[0144] Its anti-resonant structure layer 21 has a wall thickness of t = 0.37 μm (m = 1), and the micro-cladding layer 22 has α = 1.2 and n in =1.47, n out =1.43.

[0145] Its metal nanoparticles are Au nanorods with an aspect ratio of 3:1, resulting in a transverse LSPR of approximately 520 nm and a longitudinal LSPR of approximately 650 nm. The longitudinal peak is used to generate polarization-dependent loss, with a detuning of 22% and a concentration κ=1.0.

[0146] like Figure 4 The figure shows the curve of bending loss as a function of the gradient exponent α in this embodiment, with bending radius R. b =5cm.

[0147] When α=0, corresponding to the conventional HC-ARF without gradient layers, the bending loss is as high as 3.5dB / turn; as α increases, the bending loss first decreases rapidly, reaches a minimum of 0.5B / turn at α=1.2, and then slightly recovers.

[0148] This verifies that the presence of the gradient refractive index of the microcladding 22 can significantly suppress mode field distortion and leakage caused by bending; and that there exists an optimal α value that allows the optical fiber to achieve minimum bending loss while maintaining low confinement loss. Compared to conventional hollow-core antiresonant optical fiber, this embodiment reduces bending loss by 86%, enabling the optical fiber to operate stably under a small radius bend of 5 cm.

[0149] Example 3 provides a tunable nonlinear optical fiber for the 3μm mid-infrared band. Its inner cladding consists of eight anti-resonant units 2 arranged at equal intervals along the circumference.

[0150] Both the anti-resonance structure layer 21 and the micro-cladding layer 22 are made of chalcogenide glass As2Se3, and the n of the anti-resonance structure layer 21 is... g =2.8, λ0=3 μm, m=2, t=1.84 μm; its microcladding 22 has n in =2.8, n out =2.4, α=1.5.

[0151] Its metal nanoparticles are Ag nanospheres, D p =20 nm, λ LSPR =3.2 μm (6.7% detuned to pump light 3.0 μm), concentration κ=2.0.

[0152] In terms of preparation method, unlike steps S1-S4, a gradient glass tube is prepared by rotation method, and an As2Se3 film layer is deposited on the inner wall; the drawing temperature is 350℃, and the drawing environment is an inert atmosphere.

[0153] like Figure 5 As shown, the spectral broadening of the input pulse, conventional HC-ARF output, and the LSPR-enhanced fiber output of this invention are compared. With an input pulse of 5 ps, a peak power of 10 MW, and an operating wavelength of 3 μm, the conventional fiber only exhibits slight broadening, resulting in an output pulse width of 600 fs, while the fiber of this invention shows a significantly wider spectral width. LSPR =3.2 μm, its output spectrum is significantly broadened to 2.5-3.5 μm, corresponding to pulse compression to 120 fs.

[0154] This verifies that detuning the operating wavelength with the LSPR peak can enhance the local Kerr nonlinearity by about 50 times. By reasonably setting this detuning amount, linear absorption of the fundamental mode can be avoided, and extremely strong nonlinear modulation can be obtained. Unlike conventional optical fibers, which cannot actively control nonlinearity, this scheme achieves tunable and highly efficient pulse compression in hollow optical fibers.

[0155] Example 4 provides a hollow-core optical fiber for 1.06μm high-power lasers.

[0156] Its anti-resonant structure layer 21 has λ0=1.06 μm, m=1, and t=0.38 μm; its micro-cladding layer 22 adopts a segmented design, and the inner layer r / R of the micro-cladding layer 22 is... m =1~1.3, α=1.2, achieving near-zero flat dispersion. Other parameters are consistent with Example 1.

[0157] like Figure 6As shown, the group velocity dispersion (GVD) of conventional HC-ARF and the fiber of this invention in the 1.06μm band is compared. The GVD of conventional fiber is about 20 ps / nm / km and varies drastically with wavelength; the fiber of this scheme has a GVD ≤ ±1 ps / nm / km in the range of 1.03-1.09μm, and has a zero dispersion point at 1.06μm.

[0158] This verifies that the gradient exponent α is an effective parameter for adjusting waveguide dispersion. The dispersion slope and null position can be independently controlled through segmented design. The near-zero flat dispersion enables the fiber to transmit high-power ultrashort pulses without significant time-domain broadening. In actual measurements, a 100W, 10ps pulse was transmitted for 200m with a broadening of less than 5%.

[0159] This invention breaks through the dispersion tuning limitation of conventional HC-ARF, namely, the dispersion of conventional HC-ARF is uniquely determined by the core diameter, and it is impossible to tune it without changing the geometry.

[0160] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the above principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A hollow antiresonant optical fiber enhanced with microcladding and LSPR, characterized in that, include: The fiber core (1), located at the center of the optical fiber, is used to guide the light wave to propagate along the axial direction. The fiber core (1) is made of a low refractive index medium. The cladding structure, located around the core (1), includes M anti-resonant units (2) distributed circumferentially. The anti-resonance unit (2) includes an anti-resonance structure layer (21) for forming an anti-resonance reflection interface to confine the light field in the fiber core (1); The anti-resonant structure layer (21) is covered with a micro-cladding layer (22) on the outer side of the optical fiber in the radial direction. The micro-cladding layer (22) has a non-resonant reflection mechanism. When the light field enters the micro-cladding layer (22), its propagation path is bent and guided back to the fiber core direction. The micro-cladding layer (22) contains a metal nanostructure, which generates local surface plasmon resonance enhancement in the micro-cladding layer (22), making the micro-cladding layer (22) a functional layer for dynamic control of optical fiber conduction characteristics.

2. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 1, characterized in that: The anti-resonance structure layer (21) is an arc-shaped cross-section structure, with the side facing the fiber core (1) being the open side, and both sides being low-refractive-index media.

3. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 2, characterized in that: The refractive index of the micro-cladding (22) decreases monotonically from the inside to the outside along its own radial direction.

4. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 3, characterized in that: The refractive index distribution of the micro-cladding (22) satisfies: , ; Where, n in R is the refractive index of the material at the inner surface of the microcladding (22). in R is the inner diameter of the microcladding (22). out The outer diameter of the micro-cladding layer (22); the refractive index n of the material at the inner surface of the micro-cladding layer (22) in The value ranges from 1.44 to 2.80, and the refractive index n of the material at its outer surface is... out The value range of is 1.40 to 2.40; α is the gradient exponent, and its value range is 0.5 ≤ α ≤ 2.

0.

5. The microcladding and LSPR-enhanced hollow anti-resonant optical fiber according to claim 3, characterized in that: The metal nanostructure includes a plurality of metal nanoparticles (221), which are uniformly or gradiently dispersed in the matrix of the microcoating (22).

6. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 5, characterized in that: When the plurality of metal nanoparticles (221) are gradient dispersed in the matrix of the microcoating (22), their concentration monotonically increases radially from the inside to the outside, and their distribution satisfies: ; Where C0 is the maximum concentration. This is the concentration distribution index, and its value ranges from 0.5 to 1. ≤2.

0.

7. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 5, characterized in that: When the metal nanoparticles (221) are spherical, the metal nanostructure can match the LSPR wavelength of the high-order modes that need to be suppressed in the optical fiber by selecting the material, particle size and concentration distribution of its metal nanoparticles (221). Among them, the characteristic size D of the metal nanoparticles (221) p The local surface plasmon resonance condition under the spherical electrostatic approximation is satisfied as follows: , when D p =λ LSPR ; Where, λ LSPR For the target local surface plasmon resonance wavelength, ε m ε is the real part of the dielectric constant of the metal nanoparticle material. eff The effective dielectric constant of the micro-cladding (22) in the particle distribution region is denoted as .

8. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 5, characterized in that: When the metal nanoparticles (221) are non-spherical, an anisotropic LSPR response is generated by directionally arranging the metal nanoparticles (221), introducing polarization-dependent loss in the optical fiber that is complementary to geometric birefringence.

9. The microcladding and LSPR-enhanced hollow antiresonant optical fiber according to claim 5, characterized in that: The anti-resonance structure layer (21) is composed of one or more anti-resonance glass film layers, and the material is silicon dioxide or chalcogenide glass; the matrix of the micro-cladding layer (22) is silicon dioxide doped with GeO2 or B2O3, or chalcogenide glass with a graded composition; the material of the metal nanoparticles (221) is one of gold, silver, platinum, copper or an alloy thereof.

10. A performance tuning method for a hollow anti-resonant optical fiber according to any one of claims 6-9, characterized in that: By adjusting the gradient exponent α to change the propagation path of the light field within the microcladding (22), the lowest bending loss can be obtained. By adjusting the gradient exponent α to continuously change the zero-dispersion point position and dispersion slope of the optical fiber, the zero-dispersion wavelength can be shifted within the target band. By adjusting the gradient exponent α and the concentration distribution exponent This minimizes the total fiber loss at the target wavelength. By selecting the shape, particle size, and concentration distribution of the metal nanoparticles (221), their LSPR wavelength λ can be optimized. LSPR Matching or detuning to the target operating wavelength λ0 to control the absorption effect or local field enhancement effect; For high-power ultrashort pulse transmission, by setting λ LSPR The detuning from λ0 is 5%-15%, which prevents the LSPR from absorbing fundamental mode energy and enhances Kerr nonlinearity through hotspot effect to compensate for self-phase modulation and suppress pulse distortion. For selective mode suppression, by adjusting λ LSPR It matches the resonant wavelength of higher-order modes, preferentially absorbs higher-order mode energy, and improves single-mode purity.